What we need to know about the Delta variant - Hassan, Taimoor (Pakistan Armed Forces Medical Journal, 2022)
As the COVID-19 pandemic is exacerbating around the globe, health pantheons are closely watching various coronavirus mutations and variants which might be more infectious than its parent strain. It is a peculiarity of viruses that viruses instantly adapt and survives to change, and variants come out when a specific strain of virus notice one or more mutations which contradict from other of its kind. The World Health Organization (WHO) and Centre for Disease Control (CDC) closely detect these variations to figure out if the transmission can lead to an escalation in COVID-19 mortalities and cases as well as it also determines that whether the vaccines are effective or not. United States classify these variants as ‘Variant of high consequence’, it compromises the effectivity vaccines and subordinate the treatments; ‘variant of concern’, this variant reported rapid transmission and severe disease; ‘variant of interest’, this kind lead outbreaks widespread.